Hydrated eutectic electrolyte with ligand-oriented solvation shell to boost the stability of zinc battery - Han, Mingming (2022)
An electrolyte cation additive strategy provides a versatile route for developing high-energy and long-life aqueous zinc-ion hybrid capacitors. However, the mechanisms of energy storage and Zn anode protection are still unclear in Zn-based systems with dual-ion electrolytes. Here, a dual charge storage mechanism for zinc-ion hybrid capacitors with both cations and anions adsorption/desorption and the reversible formation of Zn4SO4(OH)6·xH2O enabled by the Mg2+ additive in the common aqueous ZnSO4 electrolyte are proposed. Theoretical calculations verify that the self-healing electrostatic shield effect and the solvation-sheath structure regulation rendered by the Mg2+ additive account for the observed uniform Zn deposition and dendrite suppression. As a result, an additional energy storage capacity of ≈50% compared to that in a pure 2 m ZnSO4 electrolyte and an extended cycle life with capacity retention of 98.7% after 10 000 cycles are achieved. This work highlights the effectiveness of electrolyte design for dual-ion carrier storage mechanism in aqueous devices toward high energy density and long cycle life.